Frontal cutaneous and bone sarcoidosis: an example of the contiguous spread of granulomas - Braga, Sara; Jeny, Florence; Latrasse, Marjorie; Saidenberg Kermanac’h, Nathalie; Tran Ba , Stéphane; Nunes, Hilario (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2023)
Sarcoidosis is a multisystemic granulomatous disease of unknown origin. It has been argued that the skin is one of the entry doors of the possible antigen that causes sarcoidosis and after entering the skin, the causal agent may progress to the underlying bone.We report four cases with development of sarcoidosis in old scars located on the forehead, and contiguous bone involvement of the frontal bone.In most cases scar sarcoidosis was the first manifestation of the disease, and in most cases it was asymptomatic. Two patients never required treatment, and in all cases the frontal problem improved or remained stable spontaneously or under sarcoidosis treatment.Scar sarcoidosis in the frontal area may have contiguous bone damage. This bone involvement does not seem to be associated with neurological extension.